2013
DOI: 10.1007/s00299-013-1386-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA genetic polymorphism in thirteen rice cytoplasmic male sterile lines

Abstract: Thirteen rice CMS lines derived from different cytoplasms were classified into eight groups by PCR amplification on mtDNA. The orf79 gene, which causes Boro II CMS, possibly results in Dian1-CMS. Thirteen rice cytoplasmic male sterile (CMS) lines derived from different cytoplasms are widely used for hybrid rice breeding. Based on 27 loci on mitochondrial DNA, including single nucleotide polymorphisms and segmental sequence variations between typical indica and japonica as well as high-polymorphism segmental se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…More recently, with the mitochondrial genome sequence completely elucidated in some higher plant species, there has been an increased application of genomic approaches to study anther development and pollen reproduction, for example in the monocotyledonous plants Oryza sativa (rice) ( Notsu et al , 2002 ), Zea mays (maize) ( Clifton et al , 2004 ), and Triticum species (wheat) ( Ogihara et al , 2005 ), and dicotyledonous plants such as Arabidopsis thaliana ( Unseld et al , 1997 ), Brassica napus ( Handa, 2003 ), and Nicotiana tabacum (tobacco) ( Sugiyama et al , 2005 ). Many studies suggest that the mitochondrial genome is the carrier of fertility-related genes ( Hanson and Bentolila, 2004 ; Chen et al , 2010 ; Luo et al , 2013 ; Tang et al , 2014 ). Some of these genes and/or open reading frames (ORFs) encode pollen abortion-related proteins, such as ORF256 (7kDa) ( Song and Hedgcoth, 1994 ), ORF13 (13kDa) ( Klein et al , 2005 ), ORF138 (19kDa) ( Yasumoto et al , 2009 ), ORF288 (32kDa) ( Jing et al , 2012 ), ORF79 (8.9kDa) ( Wang et al , 2006 ; Luan et al , 2013 ), PCF (25kDa) ( Bentolila et al , 2002 ), and WA352 protein ( Luo et al , 2013 ; Tang et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, with the mitochondrial genome sequence completely elucidated in some higher plant species, there has been an increased application of genomic approaches to study anther development and pollen reproduction, for example in the monocotyledonous plants Oryza sativa (rice) ( Notsu et al , 2002 ), Zea mays (maize) ( Clifton et al , 2004 ), and Triticum species (wheat) ( Ogihara et al , 2005 ), and dicotyledonous plants such as Arabidopsis thaliana ( Unseld et al , 1997 ), Brassica napus ( Handa, 2003 ), and Nicotiana tabacum (tobacco) ( Sugiyama et al , 2005 ). Many studies suggest that the mitochondrial genome is the carrier of fertility-related genes ( Hanson and Bentolila, 2004 ; Chen et al , 2010 ; Luo et al , 2013 ; Tang et al , 2014 ). Some of these genes and/or open reading frames (ORFs) encode pollen abortion-related proteins, such as ORF256 (7kDa) ( Song and Hedgcoth, 1994 ), ORF13 (13kDa) ( Klein et al , 2005 ), ORF138 (19kDa) ( Yasumoto et al , 2009 ), ORF288 (32kDa) ( Jing et al , 2012 ), ORF79 (8.9kDa) ( Wang et al , 2006 ; Luan et al , 2013 ), PCF (25kDa) ( Bentolila et al , 2002 ), and WA352 protein ( Luo et al , 2013 ; Tang et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that cytoplasmic inheritance in rice and most of the other higher plants is typically due to maternal inheritance. However, increasing reports of the complicated mitotypes in rice seems compromising this opinion [19,26]. In the present research, paternal mtDNA was not transmitted to the progenies ( Supplementary Table S7), but the mitotypes in BIL lines were strongly differentiated ( Fig.…”
Section: Wide Crossing Alters Mitotypes Of Progeniesmentioning
confidence: 49%
“…Research in recent years shows that mtDNA is the genetic carrier (Hu et al 2014) for the occurrence of CMS, and that various plants in different types of cytoplasm contained mtDNA with distinct structures and sequences (Allen et al 2007;Alverson et al 2011;Chen and Liu 2014). At present, specific primers for identifying cytoplasmic types have been found in plants including rice (Luan et al 2013), maize (Slischuk et al 2011), rape (Zhao et al 2010), etc. By using mtDNA specific primers for PCR identification, this study found that the bands of K932MS were consistent with those of CMS-C Mo17 , further indicating that K932MS is a C-type cytoplasmic sterile mutant.…”
Section: Genetic Characterisation Of the K932msmentioning
confidence: 99%